Desejos de modernidade: o exército brasileiro e a missão militar francesa de instrução (1917-1927) - Lemos, Thiago Tremonte de (2014)
The main aim of this thesis is subsidize the comprehension of Brazilian Army s History and its modernist transformation, through the first years of operation of the French Military Mission hired by the Brazilian Government, in 1919, after tough discussion about the foreign model that the country would follow. Subsequently the choice of French instructors (instead the Germans, for example), parts of the Brazilian Army, the government and civil society, who desired modernity to the military institution, they hybridized your expectations and practices with the lessons, experiences and values from the French officers, fresh out of the Great War, as General Maurice Gamelin, first chief of the Mission . Departing from the idea that the concept of modernity, according to the Argentine anthropologist Néstor García Canclini, consists not necessarily the symmetric notions of modernism and modernization , it s discussed the process of Brazilian Army s transformation, with the French Mission, was characterized more by modernist elements that the modernizers